Primary Amenorrhea in Adolescents: A Narrative Review (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Introduction: Puberty is a transition that a girl undergoes into a reproductive woman, and its social effects are substantial. Any variation from the standard procedure might induce significant disappointment and anxiety. Primary amenorrhea denotes the lack of menarche and must be assessed about secondary sexual characteristics. Differential diagnosis may be classified according to gonadotropin levels. Conditions like Differences In Sex Development and Complex Obstructed Müllerian Duct Anomalies necessitate investigation and management at a specialised center with a multidisciplinary staff. Psychological assistance is essential throughout this procedure.Methods: It is a narrative review. An electronic search was performed on MEDLINE and PubMed to identify relevant articles from 2000 to 2025. This narrative review focuses on primary amenorrhea and the best practical approach for evaluation and management of affected adolescent females.Conclusion: Primary amenorrhea is an uncommon reason for adolescents to pursue medical consultation. Failure to detect and treat primary amenorrhea can have serious emotional, physical, and health effects. Primary amenorrhea acts as a diagnostic indicator rather than a definitive diagnosis, required further investigation and treatment of the underlying causes by physicians. This research seeks to delineate primary amenorrhea, explore its prevalence, and analyze its etiology, differential diagnosis, and potential treatments.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 30-42